STRATEGI KOMUNIKASI PARIWISATA DALAM MENINGKATKAN MINAT BERWISATA DI SUMATERA UTARA - Elisabeth Sitepu; Sabrin Sabrin (Lembaga Penenlitian dan Pengabdian kepada Masyarakat Universitas Darma Agung, 2020)
This aims at determining the tourism communication strategies in increasing tourism interest in North Sumatra s as well as things that became supporters and inhibitors in the implementation of marketing. This study uses descriptive methods qualitative that aim to describe the situation or phenomenon. The informants consisted of visitors to the study site, and the local regent/mayor, travel agent, local residents. The data used in this study is a combination of primary data and secondary data. Data collection techniques with observation, interviews and documentation. Data analysis, namely data reduction, data presentation, and conclusion. The results of the study show that the parties involved in developing l tourist attraction have carried out a pariwisata communication strategy but are not yet optimal. , pariwisata communication is carried out through advertising, public relations, Direct Marketing and personal selling. The marketing communication strategy focuses on: image, natural attraction, community support and advances in information technology. The marketing communication strategy that highlights the is the natural attraction to win competition with other tourist objects.